PENGARUH PELAKSANAAN ETIKA PROFESI DAN KECERDASAN EMOSIONAL TERHADAP PENGAMBILAN KEPUTUSAN AUDITOR - Istianingsih Sastrodiharjo; Robertus Suraji (Jurnal Ilmiah Akuntansi dan Manajemen, 2021)
This study takes a sample of independent auditors who work at the Public Accountant Firm in DKI Jakarta. The type of data used is primary data with data collection methods, namely indirect interviews by submitting a questionnaire. The analytical tool used is multiple regression This study aims to analyze the effect of the implementation of professional ethics and emotional intelligence on auditors in decision making. The results of this study are expected to show that professional ethics as measured by indentensi, integrity and objectivity; general standards and accounting principles; responsibility to clients responsibility to colleagues, responsibilities and practices have a significant effect on the auditor in decision making. Emotional intelligence as measured by self-recognition, self-control, motivation, empathy and social skills significantly influence auditors in decision making. Keywords: professional ethics, emotional intelligence, decision making.